1994
DOI: 10.1002/jemt.1070270402
|View full text |Cite
|
Sign up to set email alerts
|

Variations in mitochondrial ultrastructure and dynamics observed by high resolution scanning electron microscopy (HRSEM)

Abstract: Rat adrenal cortex was processed for high resolution scanning electron microscopy (HRSEM) to confirm tubular cristae, reported by transmission electron microscopy to be present in cortex mitochondria. Mitochondria in several other tissue and cell types were also observed and their ultrastructure confirmed by using three-dimensional, stereo, high resolution scanning electron microscopy. The mitochondria in rat and human hepatocytes as well as human skin fibroblasts grown in culture contained tubular cristae app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…Mitochondria from a variety of organisms and tissues have been described as dynamic organelles that change their shape and size and remodel their internal membranes or move to distinct cellular locations (11,36,54). These morphological transitions are greatly influenced by fusion and fission of the mitochondrial membranes and have been referred to as mitochondrial dynamics (29,46).…”
mentioning
confidence: 99%
“…Mitochondria from a variety of organisms and tissues have been described as dynamic organelles that change their shape and size and remodel their internal membranes or move to distinct cellular locations (11,36,54). These morphological transitions are greatly influenced by fusion and fission of the mitochondrial membranes and have been referred to as mitochondrial dynamics (29,46).…”
mentioning
confidence: 99%
“…The bundles of myofibrils were detected longitudinally and parallel, demonstrating the typical aspects such as studies reported by Peachey and Huxley (1962). The mitochondria show elongated and/or rounded shapes and we noted the mitochondrial crests according to report by Lea and Hollenberg (1989); Lea et al (1992Lea et al ( , 1994; Tanaka (1981Tanaka ( , 1989; Watanabe et al (1992).…”
Section: Discussionmentioning
confidence: 64%
“…We have shown, in fact, that mitochondria from a large variety of human and animal organs, have mostly tubular cristae ( Figure 5, inset) and that lamellar cristae ( Figure 5, inset) are joined to the inner mitochondrial membrane by tubular connexions. Such tubular connexions (Figure 5), that were not seen by Lea et al (1994) who used the freezing cracking method, were documented by our technique since 1995 (Riva et al, 1995a;Riva et al, 1995b). They were named crista junctions using HVTEMT (Mannella et al, 1997, Perkins et al, 1997.…”
mentioning
confidence: 85%